THE RELATIONSHIP BETWEEN DIET AND NUTRITIONAL STATUS BALANCE IN ADOLESCENTS - Dita Hasni; Ratna Ellia; Aissa Syifa Khalila; Debie Anggraini (Nusantara Hasana Journal, 2023)
Background: Nutritional status is the end result of harmony between the intake of nutrients received by the body and the needs of nutrients needed. This balance determines a person's nutritional status, which can be divided into three categories: less, normal, or excessive. The adolescent phase is a crucial period in which nutritional needs increase significantly along with rapid physical growth and developmental processes. The transition from childhood to adolescence becomes a period in which the body requires more nutrients to support these changes. In addition to physical growth, factors such as lifestyle changes and the diet of adolescents also affect their intake and nutritional needs. An unbalanced diet or lack of attention to the nutrients needed can result in insufficient or excess nutritional status. This paper aims to determine the relationship between diet and nutritional status balance in adolescents. Method: This systematic review uses the PRISMA-P protocol (Preferred Reporting item for Systemic Review and Meta-Analysis Protocol). The study was collected through searches on Google Scholar and PubMed data sources ranging from 2018-2023. Keyword search using PICO-S (Population Intervention Technique Compare Results-Study). Results: Results from journals on Google Scholar and PubMed obtained 10 journals related to the title of literature review. Conclusions: From various studies in adolescents, it can be seen that there is a relationship between a healthy diet and a balance of nutritional status.